Aluminosilicates as a Double-Edged Sword: Adsorption of Aflatoxin B1 and Sequestration of Essential Trace Minerals in an In Vitro Gastrointestinal Poultry Model - Hernández Martínez, Sara Paola; Delgado Cedeño, Armando; Ramos Zayas, Yareellys; Franco Molina, Moisés Armides; Méndez Zamora, Gerardo; Marroquín Cardona, Alicia Guadalupe; Kawas Garza, Jorge Ramsy (Molecular Diversity Preservation International, 2023)
Aflatoxins can cause intoxication and poisoning in animals and humans. Among these molecules, aflatoxin B1 (AFB1) is the most dangerous because of its carcinogenic and mutagenic properties. To mitigate these effects, clay adsorbents are commonly included in the diet of animals to adsorb the carcinogens and prevent their absorption in the gastrointestinal tract. In this study, four clays, three smectites (C-1, C-2, and C-3), and one zeolite (C-4), were compared as adsorbents of AFB1 and trace inorganic nutrients using an in vitro gastrointestinal model for poultry. Characterization of the clays using Fourier transform infrared spectroscopy revealed characteristic bands of smectites in C-1, C-2, and C-3 (stretching vibrations of Si-O, Al-O-Si, and Si-O-Si). The C-4 presented bands related to the bending vibration of structural units (Si-O-Si and Al-O-Si). X-ray diffraction analysis showed that C-1 is a montmorillonite, C-2 is a beidellite, C-3 is a beidellite-Ca-montmorillonite, and C-4 is a clinoptilolite. The elemental compositions of the clays showed alumina, silica, iron, calcium, and sodium contents. The cation exchange capacity was higher in C-3 clay (60.2 cmol(+)/kg) in contrast with the other clays. The AFB1 adsorption of C-1 was the highest (99.5%; p < 0.001), followed by C-2 (92.02%). However, all the clays also sequestered trace inorganic nutrients (Fe, Mn, Zn, and Se). Both smectites, montmorillonite and beidellite, were the most suitable for use as adsorbents of AFB1.